Territories of commons: a review of common land organizations and institutions in the European Alps - Pagot Giacomo; Šmid Hribar Mateja; Rail Lisa Francesca; Walters Gretchen; Hymas Olivier; Liechti Karina; Haller Tobias; Urbanc Mimi; Dalla Torre Cristina; Joye Jean-François; Lorenzini Sara; Bogataj Nevenka; et al. (Environmental Research Letters, 2025)
Common land organizations and institutions (hereinafter: CLOIs) have been extensively studied worldwide. However, the extent of the European ones is relatively unknown, despite studies and evidence of their long existence. This is the first comparative study on the CLOIs at a European regional scale. This study focuses on the Alps as defined by the Alpine Convention, and presents the first comprehensive review of data, and status of CLOIs across and within 6 alpine countries: Austria, France, Germany, Italy, Slovenia, and Switzerland. The aim is to assess (i) their historical evolution, (ii) their institutional arrangements and governance characteristics, and (iii) their numbers, surface, and land uses. To carry out this analysis, we used secondary data from official statistics, surveys, scientific and grey literature, legislation, and bylaws for each country and each region. The results show that CLOIs emerged in the Middle Ages and went through key changes in the 19th century, primarily due to Napoleon’s influence in reorganising public administration structures, and post-World War II centralization processes, especially in eastern European countries. In total, we accounted for between 5785 and 11 063 CLOIs, distributed across 32 types in the 6 countries; among which, CLOIs with full property rights and membership based on farmstead ownership are the most frequent. The main land use for Alpine CLOIs is forest followed by pasturelands. CLOIs holding agricultural land, such as cropland, was instead reported for only one country and was negligible. In this review we have identified and highlighted several scientific gaps for future but urgent research on Alpine commons. This review depicts the need for more systematic and cross-country data collection, which could encourage networking and innovation, stakeholder engagement, and CLOIs’ recognition in contributing to the sustainable development goals.